Conceptualisation and development of the RIPE-N model (reflective interprofessional education-network model) to enhance interprofessional collaboration across multiple health professions. Issue 5 (2nd September 2020) - Lucas, C.; Power, T.; Kennedy, D. S.; Forrest, G.; Hemsley, B.; Freeman-Sanderson, A.; Courtney-Harris, M.; Ferguson, C.; Hayes, C.
ABSTRACT: This paper describes a novel model of learning, designed to enhance interprofessional education (IPE) and interprofessional collaboration (IPC). Lessons learned, plans for sustainability and future directions for policy, practice, implementation, and curriculum training are also discussed. The RIPE-N model (Reflective Interprofessional Education – Network model) was developed for an interprofessional simulation environment involving five health professions – pharmacy, nursing, orthoptics, physiotherapy, and speech pathology with the potential to increase the number of health professions involved. The RIPE-N model was adapted from the original RIPE Model (Reflective Interprofessional Education Model), utilising unfolding multidisciplinary case from admission through to discharge. Key adaptations of RIPE to include a greater focus on professional practice and the opportunity for collaboration by all disciplines. Reflection is critical to the RIPE-N model to develop the reflective practitioner, hence the inclusion of collaborative reflective ('pause and reflect') stations aimed at improving collaborative clinical decision-making skills among diverse healthcare professionals.